Data from the project "Salt efflorescence on leather objects from the Vasa ship - part II" (project identifyer RAÄ-2021-3143) - Hacke, Marei; Berg, Helena; Sandström, Johanna; Öhrström, Lars; Mystere Amombo Noa, Francoise (Swedish National Heritage Board, 2025)
Data from the project "Salt efflorescence on leather objects from the Vasa ship - part II" (project identifyer Dnr RAÄ-2021-3143). Data from the following analytical techniques is included: 1.  Scanning electron microscopy with energy dispersive x-ray spectroscopy (SEM-EDS); 2.  Raman spectroscopy; 3. FTIR spectroscopy. Instrument reports including technical specifications of each instrument as well as a sampling protocol are included. Part I of the project is found at DOI: 10.5281/zenodo.10572840.
Keywords: Heritage Science; Vasa ship; Leather; waterlogged; organic material; Shipwreck; archaeological objects; archaeological conservation; polyethylene glycol; RAÄ-2021-3143; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi